The barbaric counter-revolution : - Rostow, W. W. (University of Texas Press, 1983)
Economist W. W. Rostow finds the roots of the problem in the phenomenon he terms the Barbaric Counter-Revolution—the effort to wring inflation out of the economic system by the rigorous application of a restricted rate of increase in the money supply. This policy was launched by the Carter administration in October 1979, reinforced by President Reagan in mid 1980, and abandoned in August 1982. In the end, it provided the United States with no mechanism for rapid recovery that did not bring with it a return to high interest rates, resumed inflation, and, soon, another recession.